Exploring the Relationship Between Religiosity and Offending Intentions Among Various Sub-Samples of Incarcerated Individuals - Cooper, Maisha N. (Crime & delinquency, 2025)
Researchers suggest an inverse relationship between criminal behaviors and a number of social bonds, including religiosity, but few studies have examined religiosity’s impact among adults, especially those known to have committed serious crimes. Utilizing survey data from a large sample of men and women incarcerated for felonies in a southwestern correctional system, we estimated a series of regressions examining the relationship between religiosity and intentions to drive drunk, controlling for a number of other social and self-control measures. We also explored possible race and sex differences in these relationships. Results support the negative relationship between religiosity and crime; and indicate that this significant relationship is similar among men and women, and also among White and African American individuals.